2018
DOI: 10.1016/j.pubrev.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of accountability for the crisis and type of crisis communication on people’s behavior, feelings and relationship with the government

Abstract: In this paper we investigated to what extent the willingness of people to take advice from the local government, people's feelings of collective efficacy and empowerment, and their relationship with the local government, is dependent on whether the local government was accountable for the crisis or not. In addition, we were interested in the influence of empathic versus neutral crisis information on people's behavior, feelings and their relationship with the local government. The results indicate that people's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 55 publications
1
16
0
2
Order By: Relevance
“…During crisis events, human behavior and the attitude towards the crisis is influenced by the information people have access to (Bakker et al 2018). For example, Panagiotopoulos et al (Panagiotopoulos et al 2014), Starbird et al (Starbird et al 2013), and Sutton & Shklovski (Sutton and Shklovski 2008) reported on the negative effects of rumors and misinformation during various crisis events, highlighting the importance of information that is issued by official sources (Crump 2011;Heverin and Zach 2010;Huang et al 2017;Waters and Williams 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During crisis events, human behavior and the attitude towards the crisis is influenced by the information people have access to (Bakker et al 2018). For example, Panagiotopoulos et al (Panagiotopoulos et al 2014), Starbird et al (Starbird et al 2013), and Sutton & Shklovski (Sutton and Shklovski 2008) reported on the negative effects of rumors and misinformation during various crisis events, highlighting the importance of information that is issued by official sources (Crump 2011;Heverin and Zach 2010;Huang et al 2017;Waters and Williams 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this assumption, predictive theory has been difficult to develop, as evidenced by the research gaps we discussed both in relation to data security breaches and more broadly earlier in the paper (see, e.g. Bakker et al, 2018). Though these data are specific to both the UK and data security breaches in two industries, these findings should make the field question the primacy of crisis response strategies compared to building more resilient organizations (see, e.g., Doerfel et al, 2013) or building crisis capacity.…”
Section: Discussionmentioning
confidence: 99%
“…, with m i being the frequency a motif belonging to an isomorphic class i occurring in a network M1 and m 1 i being the frequency a motif belonging to the same isomorphic class i occurring in a network M2. Over time, the motifs found in each pair of layers formed from the 12 emotion layers 5 show at least a weak structural similarity.…”
Section: Structural Similarities Of Emotion-annotated Networkmentioning
confidence: 99%
“…From hurricanes and earthquakes to tsunamis and landslides, these disasters caused communication blackouts, catastrophic damages to critical infrastructures, lack of resources, and humanitarian crises. During disaster events, the information that people have access to considerably shapes their behavior and attitudes towards the event [1]. Online social networks (OSNs) provide a vital communication medium where the ones affected by a disaster can share information, seek help, and bond emotionally.…”
Section: Introductionmentioning
confidence: 99%